Everyday Buddhism and Environmental Decisions in the World’s Highest Ecosystem - Spoon, Jeremy (Journal for the Study of Religion, Nature and Culture, 2015)
As Tibetan Buddhists from the Nyingma sect, the Khumbu Sherpa generally view the landscape as sacred and protected by various deities and spirits. Beliefs that humans can earn protection by following certain religious practices have traditionally provided bene?cial environmental outcomes. Changing economic conditions, including those driven by foreign tourism, however, have reduced the prevalence or changed the character of these religious beliefs and practices. Mixed quantitative and qualitative research conducted in 2004–2007, 2008, and 2011 showed both generational and market-driven changes related to how consultants conceived of the relationship between humans and nonhumans and which environmental taboos they observed. Everyday Buddhist knowledge and practice appeared to focus on fewer spiritual entities and to be hybridizing with more secular belief systems. For Sherpa who are not following place-based religious traditions, economics may motivate less sustainable decisions; other Sherpa will likely continue their practice or utilize new knowledge to support sustainable environmental behavior.